Transformation der Arbeit durch die Einführung neuer digitaler Technologien - Toralf Pusch; Muhamed Kudic; Marc Gerbracht; Jacob Hochhaus (Wirtschaftsdienst, 2024)
– Using data from a survey of 3,700 German establishments, this study examines how the adoption of new digital technologies correlates with key labour market indicators: new hires, workload intensification and workforce qualifications. Findings from interviews reveal a mixed impact of digitalisation on job demands and employment dynamics. While some firms experience workforce relief, others face heightened workload pressures. Despite widespread adoption, there is scant evidence of significant job losses attributed to technology integration. Instead, the data suggests a modest trend towards job creation. Notably, investment in workforce training emerges as a crucial factor in managing the digital transition.
Keywords: O33; J23; M53; 330; Arbeitswelt; Technologie; Digitalisierung; Deutschland; Arbeitswelt; Technologie; Digitalisierung; Deutschland